K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

6 tháng 12 2020

\(\left(x-3\right)^3+\left(x-4\right)\left(x-2\right)-\left(3-x\right)^2\)

\(=\left(x-3\right)^3-\left(x-4\right)\left(x-2\right)+\left(x-3\right)^2\)

Đặt \(x-3=t\)

\(t^3-\left(t-1\right)\left(t+1\right)+t^2=t^3-t^2+1+t^2=t^3+1\)

\(=\left(t+1\right)\left(t^2+t+1\right)=\left(x-2\right)\left[\left(x-3\right)^2+\left(x-3\right)+1\right]\)

\(=\left(x+2\right)\left(x^2-6x+9-x+3+1\right)=\left(x+2\right)\left(x^2-7x+13\right)\)